Linear hybrid siloxane-based side chains for highly soluble isoindigo-based conjugated polymers. Issue 79 (4th September 2020) - Ding, Yafei; Jiang, Longlong; Du, Yuchang; Kim, Sanghyo; Wang, Xiaohong; Lu, Hongbo; Zhang, Guobing; Cho, Kilwon; Qiu, Longzhen
Abstract : Linear hybrid siloxane-based side chains: giving isoindigo-based conjugated polymers high electrical properties and excellent solubilities in various common organic solvents. Abstract : Three isoindigo-based conjugated polymers modified with linear hybrid siloxane-based side chains were synthesized (PIID-C m -Si7, m = 5–7). All polymers showed good solubilities in halogenated hydrocarbons, aromatic hydrocarbons, ethers, alkanes, and esters. The polymer films of PIID-C5 -Si7, PIID-C6 -Si7, and PIID-C7 -Si7 achieved mobilities of 0.32, 0.82, and 1.58 cm 2 V −1 s −1, respectively.